Primary care physician characteristics associated with becoming opioid agonist treatment prescribers in British Columbia: a retrospective case-control study - Dimitra Panagiotoglou; Sandra Peterson; M. Ruth Lavergne; Tara Gomes; Rashmi Chadha; Cheyenne Johnson; Rita McCracken (Harm Reduction Journal, 2025)
Abstract Background Opioid agonist treatment (OAT) is the gold standard of care for patients living with opioid use disorder. Since 2016, efforts to expand OAT access have focused on primary care physicians. This study aimed to understand how OAT-prescribing-naïve primary care physicians who began prescribing OAT differed from their peers who did not. Methods We used administrative health data to identify all patients eligible for OAT initiation between 1 January 2016 and 31 December 2019. We matched primary care visits that resulted in an OAT dispensation with visits that did not. We conducted logistic regression with generalized estimating equations to identify physician demographics and practice characteristics associated with becoming an OAT prescriber. Results Of the 4253 primary care physicians who were OAT-prescribing-naïve before 2016, 2183 (51.3%) began prescribing OAT. Physicians who practiced in rural settings (aOR = 1.78, 95% CI: 1.32, 2.40) or saw fewer than 16 patients a day (aOR = 1.46, 95% CI: 1.21, 1.75) were more likely to become OAT prescribers. The likelihood of becoming an OAT prescriber declined with the proportion of visits delivered out of office (aOR = 0.20, 95% CI: 0.16, 0.26) and years since graduation (e.g., physicians who graduated between 2000–2009 were 20% less likely to initiate (aOR = 0.80, 95% CI: 0.64, 0.99) compared with peers who graduated since 2010). Conclusions Physicians who saw fewer patients and worked across fewer settings were more likely to become OAT prescribers. However, physicians in rural settings are stepping in to address unmet demand despite resource and time constraints. Understanding the differences between physicians who become OAT prescribers and peers who do not is critical to effectively target interventions to improve OAT access in the future.